The impacto f COVID-19 related social isolation on the sexual health of brazilian women (Research, Society and Development, 2023)
Objectives: To investigate the potential repercussions of social isolation and restrictive policies on female sexual well-being during the COVID-19 pandemic. Methods: This study utilized an online, anonymous, self-administered questionnaire through the Google Forms platform as the data collection instrument. The target audience comprised sexually active women residing in Brazil. The questionnaire encompassed sociodemographic inquiries and questions containing variables related to the assessment of women's sexual activity domains using the Female Sexual Quotient (QS-F). Statistical analysis was performed using the R programming environment (version 4.2.3), with a significance level set at 5%. Results: Our study consisted of 99 women, predominantly young, single, with completed higher education, residing in the capital, and of Catholic religion. Furthermore, the majority affirmed being heterosexual, having a steady partner, without children, and not cohabitating with their partners. We observed 18.2% of women with dysfunction both before and after the pandemic, indicating stability. Conclusions: The study concludes that the sexual function of women in the studied sample did not undergo a significant alteration during the pandemic when compared to the pre-pandemic period.